PrP(C) Association with Lipid Rafts in the Early Secretory Pathway Stabilizes Its Cellular Conformation - Sarnataro, Daniela (The American Society for Cell Biology, 2004)
The pathological conversion of cellular prion protein (PrP(C)) into the scrapie prion protein (PrP(Sc)) isoform appears to have a central role in the pathogenesis of transmissible spongiform encephalopathies. However, the identity of the intracellular compartment where this conversion occurs is unknown. Several lines of evidence indicate that detergent-resistant membrane domains (DRMs or rafts) could be involved in this process. We have characterized the association of PrP(C) to rafts during its biosynthesis. We found that PrP(C) associates with rafts already as an immature precursor in the endoplasmic reticulum. Interestingly, compared with the mature protein, the immature diglycosylated form has a different susceptibility to cholesterol depletion vs. sphingolipid depletion, suggesting that the two forms associate with different lipid domains. We also found that cholesterol depletion, which affects raft-association of the immature protein, slows down protein maturation and leads to protein misfolding. On the contrary, sphingolipid depletion does not have any effect on the kinetics of protein maturation or on the conformation of the protein. These data indicate that the early association of PrP(C) with cholesterol-enriched rafts facilitates its correct folding and reinforce the hypothesis that cholesterol and sphingolipids have different roles in PrP metabolism.